CRYPTOCURRENCY VS TRADITIONAL BANKING UNRAVELING THE FUTURE OF FINANCIAL SYSTEMS - Harefa, Fati Elfina Doris; Octafian, Ray (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This research discusses the comparison between blockchain technology in cryptocurrency and banking technology infrastructure, with a focus on the dimensions of security, efficiency and scalability. Using approach Systematic Literature Review (SLR) with guidelines PRISMA, the study found that blockchain excels in decentralization and efficiency for international transactions, but has challenges in its scalability and security. On the other hand, traditional banking is more stable and efficient for domestic transactions, although it is limited in facing digitalization challenges. The implications of this research provide insight for developers and regulators to design a more efficient and safer financial system by integrating the advantages of both.